Saúde mental e trabalho: metassíntese da produção acadêmica no contexto da pós-graduação brasileira - Bastos, Juliano Almeida (2014)
It's search metasynthesis type, in order to know, describe and analyze the academic literature in the Mental health and work area in the context of Brazilian postgraduate. Developed in five phases: Exploration, Refining, Crossing, Description and Analysis. With the first takes place cataloging of all the documents present in the files of theses and dissertations of the Coordination of Improvement of Higher Education Personnel - CAPES and the Virtual Health Library - Psychology - BVS-PSI from 10 search descriptors considered representative area in the literature. In the second phase, it is found among the documents found in the previous phase, which are related to the area, by reading the title, abstract and keywords of these. In the third phase is carried out a comparative analysis in order to eliminate duplicate documents. The fourth phase describes all documents according to type: thesis or dissertation; the historical ranking; area of knowledge; geographical disposition and institutional origin. In the last phase analyzes the contents of the descriptor located 16 theses Mental health and work, the most representative among those used in the previous phases. This phase identifies the following categories: history, social demands, public policy, epistemology, method and theory. The results indicate that mental health and work has its largest production, 84% under the master; in 1989 was located first thesis; between the years 2000 to 2012 88% of the documents were produced; predominance of studies related to psychology, 56% occurs; the southeast region has 46% of production; São Paulo accounts for 30%; production is 46 IES, being USP, UFRJ, UFRGS, UNB and the UFMG that most produce. There is even those produced studies respond to historically situated social demands; the relationship with the public policies is a challenge in view of the finding that the state should protect the work also has become precarious; the field of Occupational Health underlies the area; distinct methodological strategies and theoretical frameworks are used in studies. It is concluded that the adoption of an ethnographic approach as a method and an integrative approach as theoretical framework, the results achieved can convert into practical action in favor of labor, the fundamental premise of the area, given its epistemological assumptions. In this context, the researcher is involved turning their efforts to politically coherent performance with the field of Occupational Health.